An efficient approach for digital secure communication using adaptive backstepping fast terminal sliding mode control. (June 2019) - Zirkohi, Majid Moradi
Highlights: In this paper, a simple robust controller is developed for digital secure communication in a finite time. As a novelty, Chebyshev polynomials are used to approximate the nonlinearities of the master and slave systems. To form control law by considering practical point of view just the available feedbacks are used. The proposed control approach has a fast response with a good tracking performance under the well-behaved control efforts. One advantage of the proposed method is that the structure of the proposed hybrid controller is very simple. Abstract: In this work, a simple robust controller is developed for digital secure communication between two different chaotic systems (Duffing-Holmes oscillator and chaotic gyro) with uncertainties, external disturbances, and unknown parameters in a finite time by combining adaptive backstepping and terminal sliding mode approaches. The terminal sliding mode control (TSM) provides faster convergence and higher-precision control than the conventional sliding control. However, not only the original TSM encountered singularity problem but also it needs a prior knowledge about the system to be controlled. To address these issues, a fast non-singular TSM is developed, and in the core of the proposed approach, Chebyshev polynomials are used to approximate the nonlinearities of the master and slave systems. As a result of applying the proposed approach, the synchronization and the stability of the closed-loop control system are achieved. The numerical simulation results demonstrate the effectiveness of the proposed approach.